THE IMPACT OF ENTREPRENEURSHIP EDUCATION IN HIGHER EDUCATION ON THE GROWTH OF STARTUP COMPANIES - Ian Zulfikar (Research and Development Journal of Education, 2022)
Along with the development of Information and Communication Technology, it makes it easy in all fields, including the growth of start-ups. However, many of the start-ups have difficulty developing due to various constraints such as funds, resources and market access. Entrepreneurship Education in tertiary institutions is seen as one of the solutions to this problem. The purpose of this study was to evaluate the impact of entrepreneurship education in tertiary institutions on the growth of start-up companies. This study used a quantitative method with a sample of 50 start-up companies founded by university alumni who had participated in an entrepreneurship education program. The results of the study show that entrepreneurship education in tertiary institutions has a positive and significant impact on the growth of startup companies by 75.0%. This finding implies that universities can play an important role in developing entrepreneurship and economic growth